Synthesis of Silver Nano Particles (Ag-NPs) and their uses for Quantitative Analysis of Vitamin C Tablets - Rashid, Mamun Ur; Bhuiyan, Md. Khairul Hassan; Quayum, M Emran (Dhaka University Journal of Pharmaceutical Sciences, 2013)
In the present study silver nanoparticles (Ag-NPs) were prepared by using chemical synthesis. Silver nanocolloid solution has been prepared chemically by the reduction of silver salt using sodium borohydride (NaBH4) and trisodium citrate (C6H5Na3O7.2H2O). Triangular silver nanoplates were also prepared by reducing silver salt using ascorbic acid which is a mild reducing agent. The nanoparticles were characterized by UV-VIS spectrophotometry and Scanning Electron Microscopy (SEM). The reducing character of ascorbic acid was used to determine the amount of ascorbic acid in real sample like vitamin C tablets that are available in the market of Bangladesh. Dhaka Univ. J. Pharm. Sci. 12(1): 29-33, 2013 (June) DOI: http://dx.doi.org/10.3329/dujps.v12i1.16297